2020
DOI: 10.3390/molecules25163612
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on FeI/FeII/FeIII Mechanism of the Cross-Coupling between Haloalkane and Aryl Grignard Reagent Catalyzed by Iron-SciOPP Complexes

Abstract: To explore plausible reaction pathways of the cross-coupling reaction between a haloalkane and an aryl metal reagent catalyzed by an iron–phosphine complex, we examine the reaction of FeBrPh(SciOPP) 1 and bromocycloheptane employing density functional theory (DFT) calculations. Besides the cross-coupling, we also examined the competitive pathways of β-hydrogen elimination to give the corresponding alkene byproduct. The DFT study on the reaction pathways explains the cross-coupling selectivity over the eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…A recent DFT investigation of coupling mechanisms between aryl Grignard reagents and haloalkanes supporting a Fe I /Fe II /Fe III sequence has very recently been reported by Sharma and Nakamura. 114 Another illustrative example of such a mechanism has also been reported by Norrby and coworkers, supported by Hammett studies and DFT computational modelling. 115 The cross-coupling systems involved aryl Grignard reagents and benzyl halides in the absence of exogenous ligand.…”
Section: Mechanistic Considerations I) Fe II / Fe Iii Mechanismssupporting
confidence: 53%
“…A recent DFT investigation of coupling mechanisms between aryl Grignard reagents and haloalkanes supporting a Fe I /Fe II /Fe III sequence has very recently been reported by Sharma and Nakamura. 114 Another illustrative example of such a mechanism has also been reported by Norrby and coworkers, supported by Hammett studies and DFT computational modelling. 115 The cross-coupling systems involved aryl Grignard reagents and benzyl halides in the absence of exogenous ligand.…”
Section: Mechanistic Considerations I) Fe II / Fe Iii Mechanismssupporting
confidence: 53%
“…It can be concluded that the Br atom moves from the C atom of R 2 to the iron center of 3 to form 4 and RA 1 . A similar process of C–Br activation has been reported in the previous studies …”
Section: Resultssupporting
confidence: 85%
“…A similar process of C−Br activation has been reported in the previous studies. 31 (2) The C(sp 2 )−C(sp 3 ) bond of main product P 1 from the reaction of radical RA 1 with monophenylated Fe II complex 2 in Path A is formed: The approach of the generated radical intermediate RA 1 toward Fe II ArBr complex 2 leads to the formation of complex 5. From intermediate 5, the carbon atom of the radical moves closer to the iron atom to get the fivecoordinate iron(III) intermediate 6 after passing through transition state TS 2 .…”
Section: Mechanism Of the Catalytic Cyclementioning
confidence: 99%
“…Based on the aforementioned results from the mechanistic studies and our previous investigations, we propose a plausible reaction mechanism, as shown in Scheme . The reactive haloiron­(I) intermediate I is generated by the transmetalation/reduction of iron precatalyst FeCl 2 (SciPROP-TB) with lithium organoborate 1 , starting the catalytic cycle.…”
Section: Resultsmentioning
confidence: 86%